Peningkatan Hasil Belajar Siswa pada Mata Pelajaran IPA Materi Sistem Tata Surya Menggunakan Metode Pembelajaran Role Playing di Kelas VI MI Thowalib Pesagen Gunungwungkal Pati - Lu'luul Maknun; Nur Fajrie; Irfai Fathurohman (Universitas Muria Kudus, 2024)
This research is base on problem, exist in the class VI MI Thowalib Pesagen in science subjects on the Solar System. These problems include decreased student learning outcomes, learning is less interesting and students are less engaged in their studies. This study aims to determined use roles method in improving student learning outcomes on the Solar System material in class VI Semester II MI Thowalib Pesagen Gunungwungkal Pati Academic Year 2023/2024. In the type on research is Classroom Action in the result is show in the first cycle the student in learn out the pre-action learn out come, were original 5 students (27.78%) to 11 students (61.11%) in cycle I and experience another cycle 17 students (94.44%). So it can be said Role Playing can improve student learn outcomes.